A Bibliometric Exploration of Artificial Intelligence and Cybersecurity Research: Trends, Collaborations, and Impact (2013-2023) - Asian, Jelita (Universitas Nusa Putra, 2024)
This study delves into the burgeoning field of AI and cybersecurity research, utilizing bibliometric analysis to uncover key trends, collaborations, and influential contributions from 2013 to 2023. By employing advanced techniques such as citation analysis, co-authorship networks, and keyword co-occurrence, we identify pivotal publications, leading research institutions, and emerging areas of focus. The analysis provides a comprehensive overview of the intellectual landscape, highlighting the evolution of research themes, the geographic distribution of research activity, and the extent of international collaborations. The findings offer valuable insights for researchers, policymakers, and funding agencies seeking to understand the current state and future trajectory of AI and cybersecurity research.